Arab Iranians and Their Social Media Use. Issue 2 (31st December 2020) - Al-Rawi, Ahmed; Groshek, Jacob
Abstract: Arab Iranians have a special status in Iran and the Middle East. Due to their Arab origins, they are sometimes viewed as the "other" for being different from ethnic Persians, while many Arab countries regard them as the "other" as well perceiving them as being Iranians more than Arabs. This study investigates the media landscape and conflict that is linked to the Ahwazi Arabs with special attention given to social media use. The study argues that Iranian Arabs are used as pawns by two of the regional players in the Middle East - Iran and Saudi Arabia. Within such an analogy, Ahwaz is regarded as a chessboard where geopolitics is continuously played with the systematic and well-planned use of media channels. The examination of social media outlets that are related to Arab Iranians shows that they are either pro-Sunni or pro-Shiite. The resultsindicate that there are very few followers and fans from Iran especially for the Arab Iranians' anti-government channels, while Shiite SNS outlets—particularly those originating from Iran—garner more followers from inside Iran.